Carbon rings decorated with group 14 elements: new aromatic clusters containing planar tetracoordinate carbon. (10th April 2019) - Yañez, Osvaldo; Vásquez-Espinal, Alejandro; Báez-Grez, Rodrigo; Rabanal-León, Walter A.; Osorio, Edison; Ruiz, Lina; Tiznado, William
Abstract : A simple and chemically intuitive approach is used to design ptC-containing E–C clusters (E = Si–Pb). Abstract : A simple and chemically intuitive approach is used to design ptC-containing E–C clusters (E = Si–Pb). This approach consists in replacing three or two consecutive protons from an aromatic hydrocarbon by one E2 4+ or one E 2+ fragment, respectively. In the model, electrons from E are removed from the p z orbitals, emptying them. Si–Pb favors the formation of a 3c-2e (E–C–E) σ-bond, which involves the ptC. Additionally, the π-electronic cloud is delocalized through the E-p z orbitals allowing the E atoms to effectively take part in the electronic delocalization, preserving the 4 n + 2 Hückel's rule from the parent hydrocarbon. Two aromatic monocycles and one aromatic bicycle – benzene (C6 H6 ), cyclopentadienyl anion (C5 H5 − ) and pentalene dianion (C8 H6 2− ) – have been transformed into C–E systems. After an extensive exploration of their potential energy surfaces, four new global minima with ptC are identified, resulting from the substitution of the protons by Si and Ge cations in C5 H5 − and C8 H6 2− (E3 C5 and E4 C8 ). The analysis of both the chemical bonding and the magnetic response to an external magnetic field confirms the aromatic character of these species.